A culture of curiosity - Hannan, Leonie (Manchester University Press, 2023)
This study explores the practice of scientific enquiry as it took place in the eighteenth-century home. While histories of science have identified the genteel household as an important site for scientific experiment, they have tended to do so via biographies of important men of science. Using a wide range of historical source material, from household accounts and inventories to letters and print culture, this book investigates the tools within reach of early modern householders in their search for knowledge. It considers the under-explored question of the home as a site of knowledge production and does so by viewing scientific enquiry as one of many interrelated domestic practices. It shows that knowledge production and consumption were necessary facets of domestic life and that the eighteenth-century home generated practices that were integral to ‘Enlightenment’ enquiry.